2022
DOI: 10.32598/cjns.8.29.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Photobiomodulation on Shoulder Pain, Muscle Thickness, and Function in Subjects With Adhesive Capsulitis

Abstract: Background: Adhesive capsulitis or frozen shoulder is among the most prevalent causes of pain and disability in individuals. Objectives: We aimed to evaluate the effect of Photobiomodulation (PBM) on pain, range of motion, and thickness and function of supraspinatus muscle in patients with adhesive capsulitis. Materials & Methods: Overall, 52 subjects (n=26/group) with adhesive capsulitis referring to Poorsina Hospital, physiotherapy ward, Rasht City, Iran, in 2019 participated in this study. They were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some studies presented consent, and others indicated contrary findings with the effect of LLLT on pain. Recently, Ezzati et al [29] approved that the LLLT showed better analgesic effects than normal physical therapy. However, the effects on RoM, muscle thickness, and function were insignificant in the short term and one-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies presented consent, and others indicated contrary findings with the effect of LLLT on pain. Recently, Ezzati et al [29] approved that the LLLT showed better analgesic effects than normal physical therapy. However, the effects on RoM, muscle thickness, and function were insignificant in the short term and one-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, laser applications are more effective in providing the analgesic effect. [ 28 , 29 ] However, adequate time is required to improve muscle function and the range of motion, and thus longer duration follow-up studies are required to substantiate the long-term effects of laser application.…”
Section: Discussionmentioning
confidence: 99%